Contact Burn with Blister Formation in Children Treated with Sennosides. Issue 2 (23rd January 2017) - Cogley, Kimberly; Echevarria, Andrea; Correa, Catalina; De la Torre‐Mondragón, Luis
Abstract: Eight children treated for severe constipation with sennosides unexpectedly developed contact burns with blisters secondary to the use of these laxatives. All patients wore diapers, and the injuries occurred overnight. To avoid this side effect, we recommend that patients treated with sennosides, especially those in diapers, receive the medication at a time that allows for bowel movements to occur during the day and not overnight.